Effect of a bovine manure vermicompost leachate on yield of pepper (Capsicum annuum L.) hybrid Nathalie - Eduardo Fidel Héctor Ardisana; Antonio Torres García; Osvaldo Alberto Fosado Téllez; José Lincoln Cedeño Guerra; Juan Bautista Zambrano Alcívar (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The present study was aimed to investigate the effect of a bovine manure vermicompost leachate (BMVL) on growth, total chlorophyll content and yield of pepper (Capsicum annuum L.) hybrid Nathalie. In pepper, the effects of BMVL had not been studied before. Methods Six dilutions of BMVL (1:10, 1:20, 1:30, 1:40, 1:50 and 1:60 v / v), unfertilized soil and YaraMilaTM ComplexTM chemical fertilizer were tested. The experimental design was randomized blocks with four replications. The variables measured were the height of the plants, the diameter of the stem, the number of leaves, the total chlorophyll content, the length, the circumference and the weight of the fruits in four harvests. The yield per hectare in the experimental treatments was estimated from the total weight of the fruits obtained in the four harvests and the area occupied by the plants sampled. Results No substantial agronomic differences were observed in the growth variables nor in the total chlorophyll content between the experimental treatments. The estimated yields in the plots of all BMVL dilutions did not show significant differences among themselves or with chemical fertilization, and exceeded the yields of the plants in the treatment of unfertilized soil. Conclusion The results suggest that bovine manure vermicompost leachate can become a sustainable alternative for pepper production reducing fertilizer application rates, thus diminishing the contamination of the environment.